Teknik penerjemahan ujaran sanjungan pada pidato abu ubaidah dalam kanal youtube “arab tutor” - Berliana, Dinar (Maliki Interdisciplinary Journal, 2025)
This study aims to identify and analyze the translation techniques used in translating compliments in Abu Ubaidah’s speech on the YouTube channel “Arab Tutor.” The focus of the study is on how translators convey the meaning of compliments from Arabic into Indonesian. The method used is qualitative descriptive with a content analysis approach, where data is obtained from the speech transcript and its translation. The results of the study indicate that the most dominant translation technique used is the word-for-word and literal technique, with a tendency to maintain the grammatical structure of the source language. In addition, semantic techniques were also found in some of the data, indicating the translator’s efforts to capture the meaning more accurately and communicatively.